(untitled) (Journal of Economic Research & Business Administration, 2024)
Digital platforms for crowdfunding have emerged as a breakthrough in the field of entrepreneurial finance, offering a digital channel for democratizing capital access on a worldwide level. This study demonstrates how crowdfunding platforms assist impending firms in managing worldwide finances’ intricacies while surpassing institutional and cultural obstacles through practical occurrences. This paper closely examines the social impact of these platforms as well as legislative frameworks, cultural norms, key performance indicators, and platform features. An important factor determining whether or not a crowdfunding site succeeds is its design and characteristics. The study points out that some platform features like reward tiers, equity options, and community-building tools can have an impact on investor involvement and the outcome of campaigns. Furthermore, the research showcases that crowdfunding is increasingly being used as a technique to enhance diversity and inclusion, especially among unrepresented business owners including females and ethnic minorities. The study finds optimal practices and typical problems in obtaining foreign finance by examining the success rates of businesses and how these platforms assist disadvantaged entrepreneurs. The results are intended to contribute to a more inclusive entrepreneurial environment by exposing tactics that business owners can use to optimize the potential of crowdfunding in various geographic areas. In essence, this paper intends to give practical information that can be used by politicians, private-public partners, and other stakeholders in business to promote an entrepreneurship environment that is fairer and more sustainable. Key words: digital crowdfunding, global entrepreneurship, access to capital, inclusive finance.